NAP1L1: A Novel Human Colorectal Cancer Biomarker Derived From Animal Models of Apc Inactivation - Queiroz, Cleberson J. S.; Song, Fei; Reed, Karen R.; Al-Khafaji, Nadeem; Clarke, Alan R.; Vimalachandran, Dale; Miyajima, Fabio; Pritchard, D. Mark; Jenkins, John R. (Frontiers in Oncology, 2020)
Introduction: Colorectal cancer (CRC) is the second leading cause of cancer death worldwide and most deaths result from metastases. We have analysed animal models in which Apc, a gene that is frequently mutated during the early stages of colorectal carcinogenesis, was inactivated and human samples to try to identify novel potential biomarkers for CRC. Materials and Methods: We initially compared the proteomic and transcriptomic profiles of the small intestinal epithelium of transgenic mice in which Apc and/or Myc had been inactivated. We then studied the mRNA and immunohistochemical expression of one protein that we identified to show altered expression following Apc inactivation, nucleosome assembly protein 1–like 1 (NAP1L1) in human CRC samples and performed a prognostic correlation between biomarker expression and survival in CRC patients. Results: NAP1L1 mRNA expression was increased in mouse small intestine following Apc deletion in a Myc dependant manner and was also increased in human CRC samples. Immunohistochemical NAP1L1 expression was decreased in human CRC samples relative to matched adjacent normal colonic tissue. In a separate cohort of 75 CRC patients, we found a strong correlation between NAP1L1 nuclear expression and overall survival in those patients who had stage III and IV cancers. Conclusion: NAP1L1 expression is increased in the mouse small intestine following Apc inactivation and its expression is also altered in human CRC. Immunohistochemical NAP1L1 nuclear expression correlated with overall survival in a cohort of CRC patients. Further studies are now required to clarify the role of this protein in CRC.